IMPORTANCE AND REPRESENTATION OF MORAL EDUCATION IN THE PROGRAM CONTENTS OF PRESCHOOL INSTITUTIONS - TEACHERS’ ATTITUDES (Heritage, 2023)
The main goal of the research is reflected in the analysis of educators' views on the importance and representation of moral education in the contents of the curriculum of preschool institutions, in relation to gender, age seniority and age of the teacher. The research sample consisted of 87 teachers from two preschool institutions from Novi Pazar. Among the instruments used was the scale of teachers' attitudes about moral education, formed for the purposes of this research. The results were analyzed using statistical tests t-test and ANOVA (analysis of variance), with the help of the SPSS program. Based on the results obtained, attitudes about the representation of moral education in the content of the work plan and program proved to be statistically significant in relation to gender, where female educators had more positive attitudes about the representation of the content of the work plan and program compared to male educators, as well as with the variable length of service, where educators with less work experience had more negative attitudes about the suppression of moral education in the contents of the work plan and program compared to educators with longer work experience.
Keywords: teacher, content, moral education, preschool institution